(untitled) (Research, Society and Development, 2021)
Objective: To verify what care needs to be taken by the Nursing team to pregnant women diagnosed with breast cancer during pregnancy, to analyze the strategies used by nurses in view of holistic care considering their vulnerabilities and to analyze the role of Nursing in the performance and treatment of with breast cancer during pregnancy. Method: Bibliographic in nature, with data collection in the databases, Virtual Health Library (VHL), Electronic Scientific Library Online (SciELO), Latin American and Caribbean Literature (LILACS) and PUBMED; the descriptors in health (DeCS) were: Breast neoplasms, Pregnancy, Pregnancy Maintenance, Patient nursing planning and Oncology nursing. Result: Breast cancer is the second most prevalent cancer in the world among the female population. In Brazil, mortality rates for breast cancer have taken a large proportion. The treatment is multifactorial and individual, the role of the nurse is built in conducting situations related to cancer during pregnancy, being essential for the patient, promoting information about self-care, offering emotional support, providing pain relief, encouraging and encouraging. Conclusion: It is noteworthy that Nursing is at the forefront of care for women at all levels of care, which is why these professionals need to be qualified and attentive, whatever the situation. The relevance of prevention or early detection of breast cancer during pregnancy brings with it positive factors for the prognosis of the disease.